The Correlation Between Students' Motivation in Learning English and Their Speaking Ability Among Eighth-Grade Studetns (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Speaking is one of the most important English skills for students, especially in the context of English as a foreign language (EFL). However, many students still face difficulties in speaking English confidently and fluently. Motivation is believed to be one of the key factors that can influence students’ speaking performance. This study aims to explore the relationship between students' motivation in learning English and their speaking ability among eighth-grade students at MTsN 2 Kota Bekasi, Indonesia. This research used a quantitative correlational method with a total of 32 participants. The instruments included a motivation questionnaire, a speaking performance test, and classroom observation. To analyze the data, Spearman’s rank-order correlation was applied, as the data did not meet the assumption of normality. The result showed a strong positive correlation (r = 0.633, p < 0.05) between students' motivation and their speaking ability. This indicates that students with higher motivation usually achieve better in speaking. These findings highlight how important motivation is for supporting students’ speaking ability in EFL classrooms.